Analisis Rasio Keuangan Untuk Memprediksi Pertumbuhan Laba Pada Perusahaan Property Dan Real Estate Yang Listing Di Bursa Efek Indonesia (Bei) Periode 2016-2019 - Imro’atus Sholihah; M Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aims to examine the effect of the of the Current Ratio (CR), Total Asset Turn Over (TATO), Debt to Equity Ratio (DER), Net Profit Margin (NPM) and Return On Asset (ROA) on Profit Growth in property and real estate companies for the 2016-2019. This research uses quantitative research methods. The population used is all property and real estate companies listed on the Indonesian Stock Exchange (IDX) during the study period. The sample selection was determined by purposive sampling in order to obtain a sample of 26 companies. The results showed that the CR, NPM and ROA partially affect Profit Growth. Meanwhile, TATO and DER partially had no effect on Profit Growth. The results of the study using the F test show that CR, TATO, DER, NPM and ROA simultaneously affect Profit Growth. The results of the coefficient of determination show that the variables CR, TATO, DER, NPM and ROA simultaneously have an effect of 36,6% on Profit Growth. Keywords: Current Ratio (CR), Total Asset Turn Over (TATO), Debt to Equity Ratio (DER), Net Profit Margin (NPM), Return On Asset (ROA), Profit Growth.